Late potentials and their correlation with ventricular structure in patients with ventricular arrhythmias. Issue 12 (24th November 2017) - Marstrand, Peter; Axelsson, Anna; Thune, Jens Jakob; Vejlstrup, Niels; Pehrson, Steen; Bundgaard, Henning; Theilade, Juliane
Abstract: Introduction: The presence of late potentials (LP) may indicate a predisposition to ventricular arrhythmias and sudden cardiac death. We investigated the association between presence of LP and structural cardiac anomalies assessed by magnetic resonance (CMR) in patients presenting with ventricular arrhythmias. Methods: We included 42 patients admitted with ventricular tachycardia or fibrillation who had undergone both signal‐averaged ECG recording and CMR imaging. Clinical data and CMR findings were compared in patients with and without LP. Results: The majority, 26 (62%) patients, were sudden cardiac death survivors and the remaining 16 (38%) were admitted with ventricular tachycardia. After full diagnostic work‐up, the most common diagnoses in the cohort were idiopathic ventricular tachycardia/ventricular fibrillation (25 patients, 60%) or cardiomyopathies (11 patients, 26%). LPs were positive in 29 (69%) when using the revised Task Force criteria. When comparing patients with and without late potentials, there were no significant differences in right ventricular size relative to body surface area (102 mL/m 2 vs 92 mL/m 2 ), right ventricular ejection fraction (55% vs 58%), or positive late gadolinium enhancement (29% vs 24%). Conclusions: Among patients with malignant arrhythmias, the presence of LP does not distinguish between patients with normal and abnormal RV structure or function on CMR. LP may indicate the presence of an arrhythmic heart disease beyond what can be inferred from CMR. The frequent finding of late potentials indicates that the diagnostic value of LP as an ARVC criteria should be tested in larger studies comparing ARVC patients and controls.